A new species of Microphallus (Trematoda: Microphallidae) from Venezuela - M.T Díaz; A.K Bashirullah; L.E Hernández (Revista de Biología Tropical, 2004)
During 1997-1999, a total of 94 crabs, Uca rapax were collected from La Sabana, La Ceiba and El Paujil, Sucre State, Venezuela. Of these 36 were infected with metacercariae. Two parasites were located in the abdominal muscles and one under the tissue of carapace and gonad. These metacercariae grew to adults in the following genera: Levinseniella, Microphallus and Maritrema, in the period of 2-5 days after feeding experimentally to the rat Rattus norvegicus, mice Mus musculus and duck Cairinia moschata. Specimens of the genus Microphallus were described herein as a new species M. sabanensis. The life cycle of M. sabanensis sp.nov. were studied experimentally using rat, mice and duck. All developmental stages and the adult are described. In addition, M. sabanensis was collected from wild birds Anas discors, Pluvialis squatarola, Butorides striatus, Egretta caerulea and Nycticorax violaceus from the same localities Durante 1997-1999, se recolectaron en La Sabana, La Ceiba y El Paujil del Distrito Cajigal, Estado Sucre, Venezuela, un total de 94 cangrejos Uca rapax, 36 de ellos estaban parasitados con tres especies de metacercarias de digéneos. Dos de ellos localizados en la musculatura del abdomen y una en el tejido que recubre internamente el caparazón y las gónadas. Estas metacercarias fueron dadas como alimento a ratones Mus musculus, ratas Rattus norvegicus, y patos Cairina moschata y tres genéros de microfálidos, Levinseniella, Microphallus y Maritrema fueron recuperados del intestino delgado de estos animales después de 2-5 días de la infección. Especimenes del genero Microphallus de este estudio se describen como Microphallus sabanensis sp.n. Se estudió experimentalmente los aspectos de ciclo vida de la especie, utilizando ratas, ratones y patos. Se describen todas las estapas larvales y los adultos. Además, M. sabanensis se encuentra naturalmente en las aves: Anas discors, Pluvialis squatarola, Butorides striatus, Egretta caerulea y Nycticorax violaceus